Effect of Indole Butyric Acid (IBA) Concentration on the Stem Cuttings of Melicope lunu-ankenda (Gaertn.) Hartley - Anish, M. C.; Aneesh, K. S.; Vidyasagaran, K.; Gopakumar, S. (Indian Forester, 2025)
No Abstract.